A STUDY ON THE IMPACT OF DIGITAL FINANCE ON FINANCIAL INCLUSION (International Journal of Food and Nutritional Sciences, 2022)
Ironically, a third or more of the population of developing nations is still not eligible for financial services even in the twenty-first century. Numerous studies that have been done in this direction suggest that including those who are financially excluded in banking results in both individual and social welfare. In order to assist alleviate poverty in developing and emerging economies, the G-20 nations and the World Bank have been driving the push for greater financial inclusion in developing countries since 2010 (GPFI, 2010). Policy makers and academics are paying more attention to the value of digital finance and financial inclusion for reducing poverty and boosting the economy today, largely due to the numerous problems that still exist in Digital currency and mobile technology can cater the needs of small transaction at an affordable cost. Additionally, it can facilitate quicker, more accurate, and accurate bulk transactions. Financial service users, digital finance providers, governments, and the economy all benefit from digital finance and financial inclusion, including increased access to finance for the underprivileged